2014
DOI: 10.1097/jom.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Survey of Workers Exposed to Aliphatic Diisocyanates Using Detailed Respiratory Medical History and Questions Regarding Accidental Skin and Respiratory Exposures

Abstract: Consistent with a previous study, no cases of occupational asthma were identified from exposure to 1,6-hexamethylene diisocyanate, isophorone diisocyanate, methylene bis(4-cyclohexyl isocyanate), or their polyisocyanates even though many employees reported detection of odors (93%) or skin exposures (53%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In two studies conducted in companies where air measurements did not show a reading above the exposure limits, no occupational asthma cases were identified after 20 years of retrospective follow-up [16,17]. This finding was confirmed by a shorter inception cohort study (18).…”
Section: Chemical Industrymentioning
confidence: 81%
See 3 more Smart Citations
“…In two studies conducted in companies where air measurements did not show a reading above the exposure limits, no occupational asthma cases were identified after 20 years of retrospective follow-up [16,17]. This finding was confirmed by a shorter inception cohort study (18).…”
Section: Chemical Industrymentioning
confidence: 81%
“…The risk of occupational asthma would seem to be highest for di-isocyanates (two groups on the same molecule), while the risk is not clearly established for mono-isocyanates [48]. In 2012, a literature review reported that long-term, low-intensity exposures did not appear to be more of a risk for occupational asthma as short, high exposures [49], whereas other studies reported that it is the duration of daily exposure that is predictive for the risk of occupational asthma [17,50]. However, it appears that exposures at undetectable levels may result in pulmonary symptoms such as tightness of the chest [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33] Due to the severe physiological adverse effect of inhalation of isocyanates, regulatory organizations such as the National Institute for Occupational Safety and Health (NIOSH), Occupational Safety and Health Administration (OSHA) and American Conference of Governmental Industrial Hygienists (ACGIH) have set occupational exposure limits (OELs) for these compounds at 5 ppb (Time-Weighted Average TWA) for a full work shi and 20 ppb (TWA) for a short-range exposure limit. [34][35][36] However, the estimation of isocyanate concentration in the working atmosphere is critical due to its high reactivity, volatile nature and instability. Hence, various research activities have been carried out to develop rapid and sensitive analytical techniques for the detection of airborne organic isocyanates.…”
Section: Introductionmentioning
confidence: 99%